Pengembangan Usaha Ikan Salai Patin Di Desa Pulau Gadang, Riau - Nur Afrinis; Taruna John; Nislawaty Nislawaty (Universitas Muhammadiyah Sidoarjo, 2018)
The service has been carried out in the PKK Women's Group, the residents of Turi Hamlet, Turirejo Village, Kedamean District, Gresik Regency. The service is carried out for 1 month starting from August to September 2017. The aim is to help PKK residents of Dusun Turi especially women in determining the Cost of Goods Sold in Entrepreneurship so that they can calculate all the costs that have been used while running the business and also for know how much the amount of profit and loss during running the business. Small and medium enterprises (UKM) are businesses that start from family or home businesses. By making corn brownies as SMEs, they can earn their own income by utilizing farmers' crops such as corn which can be processed into food, namely corn brownies. By making corn brownies as SMEs, this dedication tries to help PKK residents of Turi Hamlet, especially mothers, in determining the cost of sales that can be applied to corn brownies UKM.